TAX RISK MANAGEMENT: AN EMERGING TREND OR A NECESSITY? - Fernandez, Prafula (The journal of contemporary issues in business and government, 2008)
Following major corporate collapses, the US Government introduced the Sarbanes- Oxley Act of 2002 requiring, among a number of issues, management of listed companies to carry out risk assessment procedures and report this to their shareholders. This article focuses on tax risk management (TRM) and examines its evolution in Australia through the Australian Stock Exchange Principles of Good Corporate Governance provisions and the Corporations Act of 2001. In light of the recent focus by the Australian Commissioner of Taxation on TRM of large corporations, this article explores the benefits of TRM and considers how technology can assist in managing tax risks.